2017
DOI: 10.1590/s1518-8787.2017051006750
|View full text |Cite
|
Sign up to set email alerts
|

Food consumed outside the home in Brazil according to places of purchase

Abstract: OBJECTIVE This study aims to describe the places of purchase of food consumed outside the home, characterize consumers according to the places of consumption, and identify the food purchased by place of consumption in Brazil.METHODS We have used data from the Pesquisa de Orçamento Familiar (Household Budget Survey) of 2008-2009 with a sample of 152,895 subjects over 10 years of age. The purchase of food outside the home was collected from the records of all expenditures made in seven days. The places of purcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 19 publications
1
23
0
16
Order By: Relevance
“…The same may apply to other types of non-fast food restaurants. As shown by Bezerra et al 43 , individuals who eat at restaurants usually have a better education and income status. The adolescent phase of life is characterized by increased independence from their parents and family, where they begin to make their own choices, including what to eat 54,55 .…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The same may apply to other types of non-fast food restaurants. As shown by Bezerra et al 43 , individuals who eat at restaurants usually have a better education and income status. The adolescent phase of life is characterized by increased independence from their parents and family, where they begin to make their own choices, including what to eat 54,55 .…”
Section: Discussionmentioning
confidence: 93%
“…Health Survey in São Paulo City (ISA-Capital), São Paulo, Brazil, 2015. food and other informal food trades, which are not registered in the Sanitary Surveillance, is unavailable. Previous research studies have found that these establishments are used by 4.6% of Brazilians 43 . Finally, it is not possible to conduct a qualitative analysis of the food establishments listed.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations